Thermoelectric (Bi, Sb)2Te3–Ge0.5Mn0.5Te composites with excellent mechanical properties. Issue 15 (27th March 2019) - Duan, Sichen; Man, Na; Xu, Jingtao; Wu, Qingsong; Liu, Guo-qiang; Tan, Xiaojian; Shao, Hezhu; Guo, Kai; Yang, Xinxin; Jiang, Jun
Abstract : (Bi, Sb)2 Te3 composites with structure modifications by Ge0.5 Mn0.5 Te additions can simultaneously improve thermoelectric performance and mechanical properties. Abstract : (Bi, Sb)2 Te3 alloys have been widely used in thermoelectric cooling, but their poor mechanical properties limit the module size to reach higher cooling density. Here, we report the thermoelectric and mechanical properties of (Bi, Sb)2 Te3 –Ge0.5 Mn0.5 Te composites; Ge0.5 Mn0.5 Te has recently been reported to be a promising thermoelectric material with high hardness in a moderate temperature range. Alloying with Ge0.5 Mn0.5 Te not only reduces the lattice thermal conductivity, but also improves the mechanical properties. Along with carrier concentration regulation, both excellent thermoelectric and mechanical properties have been achieved in (Bi, Sb)2 Te3 –Ge0.5 Mn0.5 Te composites. The Vickers hardness increased from 0.45 Gpa for the pristine (Bi, Sb)2 Te3 to 0.81 Gpa for the sample with 1.0% Ge0.5 Mn0.5 Te, and a Young's modulus of 37.06 Gpa was obtained for the one with 1% Ge0.5 Mn0.5 Te. By adjusting the carrier concentration, the final ZT value of (Bi, Sb)2 Te3 > 1.1 at 350 K.